Environmental Characteristic of Phyllophorus sp. (Echinodermata, Holothuroidea, Phyllophoridae) Habitat in the Madura Strait, Indonesia - Widianingsih Widianingsih; Retno Hartati; Hadi Endrawati (Universitas Diponegoro, 2023)
Information on the environmental characteristics of many sea cucumber habitat is limited, despite these species exhibiting rapid exploitation and may lead to depletion. The present study combined a survey on many seawaters and sediment characteristics of habitat valuable aspidochirote holothurian, Sea Ball Cucumber, Phyllophorus sp. to compare with location with no sea cucumber in Madura Strait, Indonesia. Data from detailed surveys were used to compare both locations with measures of physical and chemical seawater parameters including temperature, salinity, dissolved oxygen, pH, phosphate, nitrate, ammonia, chlorophyll-a, total suspended solids, light transparency, and depth of water. The comparison was also carried out on physical and chemical parameters of surface sediment, i.e. phosphate, nitrate, ammonia, chlorophyll-a, grain size, total organic matter, and carbon-organic content. The data then were analyzed using Mann-Whitney U-Non Parametric Test with SPSS v. 16. The result revealed that there were significant differences between sediment characteristics of Sea Ball Cucumber habitat and no Sea Ball cucumber location, but not for seawater. Seawater parameter value in Madura Strait showed in the range required for its life. This analyzes proved the importance of sediment characteristics for Phyllophorus sp. As benthic deposit feeders, they did not only utilize substrate underneath the body for its habitat but also primarily to supply their natural food.